A study on ergonomic issues toward employees’ performance in MASkargo Sdn. Bhd. / Mohd Fikry Aminuddin - Aminuddin, Mohd Fikry (Faculty of Business and Management, 2009)
This study is focus on the ergonomic issues at MASkargo Sdn. Bhd. which has potential to affect employees’ performance. The main objective of this project paper is identify the main factor that contributes to ergonomic issues towards employees’ performance in MASkargo Sdn. Bhd. The research is focusing on employees at MASkargo Sdn. Bhd., which is consisting of 40 respondents excluded employees who work in warehouse. The theoretical framework of this study consists of dependent variable and independent variables. The dependent variable is employees’ performance while the independent variables are tasks, physical environment, workspace, and organization and procedure. Data collected and evidences are being processed by using Statistical Package for Social Science (SPSS) program. The analysis includes the reliability, frequency distribution, descriptive analysis, and correlation.